2004
DOI: 10.1055/s-2004-825634
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Animal Models for Hemophilia Gene Therapy: Predictive Value and Limitations

Abstract: Hemophilia A and B are excellent candidate disorders for the application of somatic cell gene therapy. One of the major advantages in the preclinical development of hemophilia gene therapy strategies has been the availability of several animal models for both hemophilia A and B. These models recapitulate many of the phenotypic aspects of human hemophilia and have proven to be very informative in exploring the efficacy and safety of gene therapy. Considerable progress has been made in the design of gene therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Furthermore, since prior studies have demonstrated that the hemophilia dog model, compared with the mouse model, more accurately predicts the therapeutic outcomes in humans and other primates, 32,33 we have determined the long-term efficacy and safety of AAV2-cFVIII, AAV6-cFVIII, and AAV8-cFVIII vectors in hemophilia A dogs, to assess whether dogs recapitulate the findings for different vector serotypes observed in mice. The potential application of alternative serotype AAV-FVIII vectors in humans not only may enhance the therapeutic efficacy, but also may diminish some neutralization by pre-existing anti-AAV2 antibodies that are prevalent in the human population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since prior studies have demonstrated that the hemophilia dog model, compared with the mouse model, more accurately predicts the therapeutic outcomes in humans and other primates, 32,33 we have determined the long-term efficacy and safety of AAV2-cFVIII, AAV6-cFVIII, and AAV8-cFVIII vectors in hemophilia A dogs, to assess whether dogs recapitulate the findings for different vector serotypes observed in mice. The potential application of alternative serotype AAV-FVIII vectors in humans not only may enhance the therapeutic efficacy, but also may diminish some neutralization by pre-existing anti-AAV2 antibodies that are prevalent in the human population.…”
Section: Introductionmentioning
confidence: 99%
“…The severe hemophilia A dogs in this colony have no detectable plasma levels of FVIII and have approximately 5 spontaneous bleeding episodes per year. 33 The citrated plasma from these animals fails to clot in a TEG assay when stimulated with excess calcium. As a first step, the potency of AV513 to accelerate clot initiation was compared with citrated whole blood from AAV-FVIII hemophilia dogs and the severe hemophilia A dogs in an in vitro TEG assay.…”
mentioning
confidence: 97%
“…8 In the present study, we used BAL-fVIIIKO mice (fVIII exon 16-disrupted knockout mice bred onto the BALB/c background), which have been shown to develop 3-to 4-fold higher anti-fVIII inhibitor titers following adenovirus-mediated fVIII gene delivery or subcutaneous injection of recombinant human fVIII than those congenic with the C57BL/6 strain. [31][32][33] In the current experiments, sustained expression of efVIII as well as sfVIII⌬B in the plasma of all immunocompetent hemophilia A BM transplant recipients for up to 24 weeks after transplantation implied lack of stimulation of a potent inhibitory immune response to either fVIII protein. To , and BM cells was quantified by real-time PCR using human fVIII-specific primers at 6 months after transplantation.…”
Section: Analysis Of the Anti-fviii Immune Response In Corrected Bal-mentioning
confidence: 53%
“…7,8 The goal of the present study was to obtain comparable results by using a more clinically relevant HSC gene therapy protocol that (1) uses a less genotoxic transgene delivery system, (2) minimizes both the number of vector copies per transduced cell and the dose of transduced cells that are transplanted, (3) incorporates reduced-intensity transplant conditioning regimens, and (4) uses the BAL-fVIIIKO strain of hemophilia A mice, which mounts a more potent anti-fVIII inhibitor response to exogenous fVIII than the C57-fVIIIKO strain. [31][32][33] To minimize the number of genetically modified cells needed to produce therapeutic levels of fVIII, we constructed an enhanced fVIII variant, efVIII. Several fVIII variants have been bioengineered previously which exhibit increased secretion, altered immunogenicity, or decreased degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation